Interference of TRPV1 function altered the susceptibility of PTZ-induced seizures - Jia, Yun-Fang; Li, Ying-Chao; Tang, Yan-Ping; Cao, Jun; Wang, Li-Ping; Yang, Yue-Xiong; Xu, Lin; Mao, Rong-Rong (Frontiers in Cellular Neuroscience, 2015)
Transient receptor potential vanilloid 1 (TRPV1) is widely distributed in the central nervous system (CNS) including hippocampus, and regulates the balance of excitation and inhibition in CNS, which imply its important role in epilepsy. We used both pharmacological manipulations and transgenic mice to disturb the function of TRPV1 and then studied the effects of these alterations on the susceptibility of pentylenetetrazol (PTZ)-induced seizures. Our results showed that systemic administration of TRPV1 agonist capsaicin (CAP, 40 mg/kg) directly induced tonic-clonic seizures (TCS) without PTZ induction. The severity of seizure was increased in lower doses of CAP groups (5 and 10 mg/kg), although the latency to TCS was delayed. On the other hand, systemic administration of TRPV1 antagonist capsazepine (CPZ, 0.05 and 0.5 mg/kg) and TRPV1 knockout mice exhibited delayed latency to TCS and reduced mortality. Furthermore, hippocampal administration of CPZ (10 and 33 nmol/μL/side) was firstly reported to increase the latency to TCS, decrease the maximal grade of seizure and mortality. It is worth noting that decreased susceptibility of PTZ-induced seizures was observed in hippocampal TRPV1 overexpression mice and hippocampal CAP administration (33 nmol/μL/side), which is opposite from results of systemic agonist capsaicin. Our findings suggest that the systemic administration of TRPV1 antagonist may be a novel therapeutic target for epilepsy, and alteration of hippocampal TRPV1 function exerts a critical role in seizure susceptibility.